Reclassification of the Indo-Pacific Hawkfish Cirrhitus pinnulatus (Forster) - Gaither, Michelle R.; Randall, John E. (Zootaxa, 2013)
The hawkfish Cirrhitus pinnulatus Forster (in Bloch & Schneider 1801) was regarded as one wide-ranging Indo-Pacific species, from the Red Sea and east coast of Africa to the Hawaiian Islands and the islands of French Polynesia. Schultz (1950) resurrected the name C. alternatus Gill for the population in the Hawaiian Islands and Johnston Atoll, and described the Red Sea population as a new species, C. spilotoceps, based on morphological data. Randall (1963) confirmed the differences that Schultz used to separate Cirrhitus pinnulatus into three species, but preferred to regard them as subspecies. We examined more specimens, colour photographs, and used genetic comparisons to determine the validity of the three species recognized by Schultz (1950). Combining mitochondrial cytochrome oxidase I and cytochrome b sequence data from specimens of C. pinnulatus pinnulatus from the Indo-Pacific, C. spilotoceps from the Red Sea, and C. pinnulatus maculosus from Hawai‘i, we detected levels of sequence divergence (5–12%) that support the species-level designation of C. spilotoceps. We detected no genetic differentiation but maintain the subspecies designation of the Hawaiian form based on morphological and colour differences. We found a third genetic lineage in the Indian Ocean and Western Pacific that is 5% divergent from C. spilotoceps. We refrain from designating this group as a separate subspecies until further morphological and genetic study can be completed.